(3EeJGY GdCSeGY HeG ddQShd ef GdCHfGA hGdCMhGd hGdMaOI hGdeJGYs - (3CMeO Hf Ydj Hf YHO GdbGOQ, CHh GdYHGS GdMSjfj GdYHjOj, Jbj GdOjf GdebQjRj,J (B845 (3g` s
(3ChdgG (B:s
(3HPdc jhejf Ch KdGKI Ke LGA QShd Gddg Udi Gddg Ydjg hSde hge LdhS aSde Ke LdS s
(3BNQgG (B:s
(3Cf JHjf eG ai GdcJGH ajYe hjNU hjRjO Ydjg hjTQM eG ai GdcJGH ajchf ai hLhH GdYde Hg hdRhe bHhdg s
(3Vef eLehY , JQJjHgG (B: (3GdeLdO GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B11s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B33 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B886) s
Keywords: (3GdJGQjNs